2018
DOI: 10.1136/archdischild-2017-313191
|View full text |Cite
|
Sign up to set email alerts
|

Parent-reported prevalence and persistence of 19 common child health conditions

Abstract: Beyond infancy, most Australian children are experiencing at least one ongoing health condition at any given time. This study's age-specific estimates of prevalence and persistence should assist families and clinicians to plan care. Conditions showing little resolution (obesity, asthma, attention-deficit hyperactivity disorder) require long-term planning and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
2
23
0
1
Order By: Relevance
“…While some health problems appear to be comparable with parent‐reported rates for all Australian children (e.g. asthma, sleep problems), others were more prevalent among the study cohort than Australian children, although possibly in line with some global general prevalence rates (e.g. eczema, abdominal pain, constipation and soiling) .…”
Section: Discussionsupporting
confidence: 88%
“…While some health problems appear to be comparable with parent‐reported rates for all Australian children (e.g. asthma, sleep problems), others were more prevalent among the study cohort than Australian children, although possibly in line with some global general prevalence rates (e.g. eczema, abdominal pain, constipation and soiling) .…”
Section: Discussionsupporting
confidence: 88%
“…Additional articles were identified through reference tracking of included studies. Studies were eligible for review if they (1) reported randomized controlled trials (RCTs) published between 1990 and September 2018, (2) evaluated an integrated health care intervention designed to improve CYP's health, (3) included CYP (0-18 years) with an ongoing health condition (defined as any health problem requiring clinical follow-up for .12 months in 50% or more cases), 26 (4) included at least 1 health-related outcome indicator, and (5) were a peer-reviewed publication available in English. Eligible articles were screened to identify references reporting additional results from the described intervention, which were included if they assessed the same intervention and sample as the original article.…”
Section: Methodsmentioning
confidence: 99%
“…Child mortality has decreased markedly over the last 50 years, and the epidemiological transition toward chronic conditions, such as asthma and neurodevelopmental disorders, applies across many countries and regions. [1][2][3][4][5] These broad populationlevel changes mean that health systems and health care models must adapt accordingly, providing highquality care for all childhood conditions.…”
mentioning
confidence: 99%
“…Recent parent‐reported data on the prevalence of constipation in the Australian population found 4% of children affected at age 8 years. Other studies, depending on the definition used and the study methodology, have found as much as 26% of children affected .…”
Section: Introductionmentioning
confidence: 99%